THE INFLUENCE OF PRODUCT DIVERSITY AND CUSTOMER RELATIONSHIP MANAGEMENT ON LOYALTY CUSTOMERS THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE ( Case Study of Bo Cafe & Resto Tebing Tinggi ) - Wahyu Ginanjar; Rotua Sri Linda Sitompul; Dara Mustika; Mangasi Sinurat; Rapat Piter Sony (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
management on customer loyalty through customer satisfaction as an intervening variable (case study of Bo Cafe & Resto Tebing Tinggi). The research method used is a quantitative method using the help of Smart PLS version 3.0 which was collected from the results of distributing questionnaires to 96 consumers of Café BO & Resto Tebing Tinggi. The analytical method used in this research is using instrument tests, namely validity and reliability tests. measurement model (outer model), namely validity test, reliability test, then the structural model (inner model) includes: coefficient of determination/r-square (r2), goodness of fit model and hypothesis testing with the t-statistic test and indirect effect test (indirect influence). The results of Smart PLS 3.0 in this research are that Product Diversity has no effect on Customer Satisfaction, Customer Relationship Management has an effect on Customer Satisfaction, Product Diversity has an effect on Customer Loyalty, Customer Relationship Management has an effect on Customer Loyalty, meaning that Customer Satisfaction has no effect on Customer Loyalty, Customer Satisfaction cannot mediate the influence of Product Diversity, Customer Satisfaction cannot mediate the influence of Customer Relationship Management on Customer Loyalty.